2004
DOI: 10.1002/eat.20025
|View full text |Cite
|
Sign up to set email alerts
|

Associations among aspects of impulsivity and eating factors in a nonclinical sample

Abstract: The lack of association between cognitive restraint and impulsivity suggests that they are functionally distinct. Disinhibition is most closely associated with impulsivity, consistent with findings from clinical samples. Further clarification of the relationship between impulsivity and eating in nonclinical populations could facilitate a better understanding of the relationship between personality variables and normal eating behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 13 publications
5
41
0
2
Order By: Relevance
“…Our results are also in line with previous studies reporting an association of eating psychopathology with the attention components of impulsiveness, but not with the executive ones [31]. In fact, the generators of the P3 elicited by target stimuli were comparably active in both BN patients and HCS, while the generators of the P3 elicited by irrelevant stimuli were hyperactive in patients with BN compared to HCS, thus demonstrating inappropriate allocation of attentional resources to irrelevant stimuli.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are also in line with previous studies reporting an association of eating psychopathology with the attention components of impulsiveness, but not with the executive ones [31]. In fact, the generators of the P3 elicited by target stimuli were comparably active in both BN patients and HCS, while the generators of the P3 elicited by irrelevant stimuli were hyperactive in patients with BN compared to HCS, thus demonstrating inappropriate allocation of attentional resources to irrelevant stimuli.…”
Section: Discussionsupporting
confidence: 92%
“…Even in non-clinical samples, impulsivity correlates with some aspects of eating behaviours, in particular eating disinhibition [103] , and seems to be a risk factor for ED behaviours [104] . A recent study on a large non-selected adolescent population sample found an association between bulimic behaviours and discontrol behaviours (bullying, truancy, excessive drinking, sexual dishinibition) [105] .…”
Section: Impulsivitymentioning
confidence: 99%
“…We believe that the answer is yes, but important qualifications must be offered. First, impulsivity is a predictor of bulimic symptoms (Claes et al 2006;Lyke and Spinella 2004), but it is also thought that that there are subgroups of bulimia nervosa patients, some of who are compulsive rather than impulsive (Engel et al 2005). Our cognitive control model has specific relevance to understanding impulsivity-driven symptoms, but is unlikely to account for other pathways toward bulimia nervosa.…”
Section: Toward the Clinical Relevance Of Individual Differences In Cmentioning
confidence: 99%
“…Moreover, higher levels of impulsivity have been linked to a wider variety of purging methods (e.g., vomiting, laxatives, diuretics: Stein et al 2004), as well as to an increased tendency toward other impulsive behaviors such as suicide attempts (Stein et al 2004) and self-harming behavior (Casillas and Clark 2002). Thus, there are multiple sources of data linking trait impulsivity to bulimic symptoms, with further suggestions that the presence of impulsive traits influences the form and severity of such symptoms (Claes et al 2006;Lyke and Spinella 2004).…”
Section: Impulsivity As a Risk Factor For Bulimic Symptomsmentioning
confidence: 99%